Modification of lignin from pulping black liquor for production of lignin-phenol-formaldehyde adhesive - Lim, KahYen (2023)
Black liquor, a complex pulping by-product, contains lignin residues, degraded carbohydrates, and inorganic constituents. To release cellulose fibres, lignin, hemicelluloses, and other wood extractives were removed from wood during pulping. It is a main pollutant from conventional paper mills. However, sustainability and environmental awareness have drawn attention to black liquor's main ingredient, lignin. Lignin could replace non-renewable chemical feedstocks. The study aimed to investigate the potential to utilise lignin from oil palm empty fruit bunch black liquor (OPEFB-BL) from Preconditioning Refiner Chemical- Recycle Bleached Mechanised Pulping (PRC-RBMP) and increase its chemical reactivity for the production of lignin-phenol-formaldehyde (LPF) adhesive. This study had a four-part design. The first part of the study determined OPEFB-BL composition and characteristics from PRC-RBMP. Secondly, lignin extraction from PRC-RBMP OPEFB-BL was optimised at pH 2.5-3.5, 40-60 °C, and 0.5-1.5 hours, and were characterised by phenolic hydroxyl content and FT-IR analysis. Thirdly, lignin was phenolated and microwave pyrolysed to increase its chemical reactivity. The lignin was phenolated and optimised in the condition range of lignin/phenol ratio (1:2 to 2:1), 80-120 °C, 30-110mins and H2SO4 catalyst dosage between 2-10%. For microwave pyrolysis, the yield of bio-oil produced was obtained at 7 different powers between 600-1200 W. Both modified-lignins were evaluated by their phenolic hydroxyl contents and FT-IR analysis. Lastly, LPF resins were synthesized using two types of modified lignin with different percentages of lignin to phenol replacement (5%, 10%, 15%, 20%, 25% and 30%). The selected adhesives were applied on rubberwood veneers to determine its shear strength. PRC-RBMP black liquor lignin had similar properties to hardwood and softwood lignin. EFB lignin was mostly guaicyl (G) and syringyl (S). Lignin extraction at pH 3.0, 1 hour, and 60 °C enables extraction of lignin with 1.268 mmol/g phenolic hydroxyl. Phenolation and microwave pyrolysis have increased the chemical reactivity of extracted lignin relative to phenolic hydroxyl content. The phenolic hydroxyl content of phenolated lignin under the optimised condition of 1:1 L/P ratio, 110 mins, 100 °C and 8% H2SO4 is five-folds that of extracted lignin; while that of bio-oil produced from 1000W microwave pyrolysis is 15.5 folds that of extracted lignin. PRC-RBMP EFB lignin showed promise as plywood adhesive for LPF resins. LPF and PF share functional groups and similar properties. Phenolated lignin had better viscosity and solid content than bio-oil in plywood adhesive synthesis, indicating that it reacts better with formaldehyde. Plywood bonded with 5% and 10% phenolated lignin resin had higher shear strength (1.61 to 1.78 MPa) than unmodified lignin (1.05 MPa) but lower than control PF (2.72 MPa). 5% and 10% phenolated lignin LPF (ELPF) yield satisfactory results. 5%ELPF performed better than 10%ELPF. This research helps us understand PRC-RBMP OPEFB-BL and modified lignins in LPF resin's properties. Lignin extracted from black liquor can be used in a variety of biopolymer applications, providing a second source of income to the pulping industry, reducing production waste, waste water treatment costs, petrochemical use, and environmental pollution. The industry would benefit economically, environmentally, and socially by completing the study and continuing research.